2022
DOI: 10.3390/s22082953
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motion Analysis Systems in Tracking Upper Body Movement of Myoelectric Bypass Prosthesis Users

Abstract: Current literature lacks a comparative analysis of different motion capture systems for tracking upper limb (UL) movement as individuals perform standard tasks. To better understand the performance of various motion capture systems in quantifying UL movement in the prosthesis user population, this study compares joint angles derived from three systems that vary in cost and motion capture mechanisms: a marker-based system (Vicon), an inertial measurement unit system (Xsens), and a markerless system (Kinect). Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Compared to previous work (Uhlenberg et al, 2022), and similar to the lower limbs analysis, a minor increase in median RMSE by 1.5 • was observed for upper limbs. In comparison, Wang et al (2022) reported median RMSE for their 5-IMU system ranging between 23.8−62.6 • , with overall median RMSE below 30 • across activities including grasping, lifting small/heavy objects, and reaching overhead. IMUs were mounted at one side of the upper body only and tended to overestimate shoulder rotation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared to previous work (Uhlenberg et al, 2022), and similar to the lower limbs analysis, a minor increase in median RMSE by 1.5 • was observed for upper limbs. In comparison, Wang et al (2022) reported median RMSE for their 5-IMU system ranging between 23.8−62.6 • , with overall median RMSE below 30 • across activities including grasping, lifting small/heavy objects, and reaching overhead. IMUs were mounted at one side of the upper body only and tended to overestimate shoulder rotation.…”
Section: Discussionmentioning
confidence: 97%
“…For upper limbs Goodwin et al (2021) investigated humeral elevation in individuals with spinal cord injury and showed that shoulder motion was highly consistent with MoCap. In a study by Wang et al (2022), joint angles obtained from five IMUs positioned on one side of the upper body were compared with a markerless MoCap system and a standard marker-based method. The findings indicated that the RMSE for joint angles was smaller at the shoulders compared to the elbows.…”
Section: Related Work Imu-based Joint Kinematicsmentioning
confidence: 99%
“…As such, our suite of control metrics is not solely reliant on motion capture data for metrics calculations. Alternative sources that capture grip aperture and wrist rotation data (such as from device motor positions), along with shoulder flexion/extension data (such as from markerless motion capture technology or IMUs [ 91 ]) can be used for these calculations. Furthermore, other methods of segmenting functional tasks into Reach, Grasp, Transport, and Release phases (such as segmenting markerless motion capture data or IMU-captured data) can be implemented in preparation for metrics calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional motion capture systems or optoelectronic systems, such as Vicon (Oxford, UK), MotionAnalysis (Santa Rosa, CA, USA), OptiTrack (Corvallis, OR, USA), or Qualisys (Göteborg, Sweden) [9], offer precision and reliability, among other advantages. As a result, optoelectronic systems have become a gold standard and have been used as benchmark systems in the validation of other proposals, especially in fields related to human healthcare [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%